Perubahan Sosial Ekonomi Petani Agroforestri Berbasis Kopi di Kabupaten Jember Jawa Timur - Munailatis Zahro; Sri Subekti; Lenny Widjayanthi (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
This study aimed to explain the changing both in social and economic aspects of farmers as a result of forest conversion process to agroforestry system in Harjomulyo Village, Jember Regency. This study used qualitative research. The information gained from informans who were selected purposively through snowball sampling. Observation, interview and documentational study were methods which were used to collect information. Triangulation technique also used in this study to check the validity of information. This study used interactive model of Miles & Huberman which consists of data reduction to conlusion. The result of this study showed that socio change occured farmer coorperation with Perhutani. While in economic change showed that economic condition increase, saving insurance credit, and availability tuition fees for children.